1967
DOI: 10.1002/1097-0142(196709)20:9<1351::aid-cncr2820200902>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Selective heat sensitivity of cancer cells. Biochemical and clinical studies

Abstract: Biochemical and clinical studies have revealed a profound and selective toxic effect of elevated temperatures on tumor cells. Whereas the oxygen uptake of Novikoff hepatoma and Ehrlich ascites carcinoma cells was considerably less at 427deg;C than at 38°C, there was little difference in respiration at these two temperatures in normal and regenerating liver. The inhibition of the respiration of Novikoff hepatoma cells was irreversible after 90 min. There was no significant effect of temperature on anaerobic gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
208
0
8

Year Published

1971
1971
1981
1981

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 746 publications
(220 citation statements)
references
References 36 publications
4
208
0
8
Order By: Relevance
“…These findings are in accord with previous work in which it was demonstrated that irreversible inhibition of respiration in SDB cells was correlated with inability of the cells to multiply in vitro and to produce tumours in the host (Dickson and Shah, 1972). A similar inhibition of respiration at 42 0C with concomitant maintenance of anaerobic glycolysis has been reported for Novikoff cells (Cavaliere et al, 1967) and for cells freshly obtained from solid tumours of the rabbit (Dickson and Muckle, 1972) and rat (Dickson and Suzangar, 1974). In the case of the latter two tumour types, the treated cells failed to take on transplantation into host animals.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are in accord with previous work in which it was demonstrated that irreversible inhibition of respiration in SDB cells was correlated with inability of the cells to multiply in vitro and to produce tumours in the host (Dickson and Shah, 1972). A similar inhibition of respiration at 42 0C with concomitant maintenance of anaerobic glycolysis has been reported for Novikoff cells (Cavaliere et al, 1967) and for cells freshly obtained from solid tumours of the rabbit (Dickson and Muckle, 1972) and rat (Dickson and Suzangar, 1974). In the case of the latter two tumour types, the treated cells failed to take on transplantation into host animals.…”
Section: Discussionsupporting
confidence: 91%
“…As a therapeutic modality, heat has received intermittent attention since the latter years of the last century with some impressive results in the treatment of animal and human cancer (Cavaliere et al, 1967;Suit and Schwayder, 1974;Dickson and Suzangar, 1976). Before hyperthermia can warrant more widespread clinical application, more information is required on the strategy of heating tumours, and better methods of applying heat are needed, both locally to the tumour and generally to the host, than those now available.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the oft-cited importance of both aerobic and anaerobic glycolysis in cancer cell metabolism (Busch 1962;Pitot 1966), and the specific positive correlation between anaerobic glycolysis and growth rate in hepatomas (Burk et al, 1967) Recent work in man has show-n that hyperthermia, achieved by regional perfusion (Cavahere et al, 1967;Stehlin, 1970) (Cavaliere et al, 1967). The use of hyperthermia for the treatment of cancer, although of undoubted effectiveness in the cases reported to date, has involved considerable hazard to the patient.…”
Section: Discussionmentioning
confidence: 99%